2006
DOI: 10.1038/sj.onc.1210045
|View full text |Cite
|
Sign up to set email alerts
|

P53 in blind subterranean mole rats – loss-of-function versus gain-of-function activities on newly cloned Spalax target genes

Abstract: A tumor suppressor gene, p53, controls cellular responses to a variety of stress conditions, including DNA damage and hypoxia, leading to growth arrest and/or apoptosis. Recently, we demonstrated that in blind subterranean mole rats, Spalax, a model organism for hypoxia tolerance, the p53 DNA-binding domain contains a specific Arg174Lys amino acid substitution. This substitution reduces the p53 effect on the transcription of apoptosis genes (apaf1, puma, pten and noxa) and enhances it on human cell cycle arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…50,51 In addition, a mouse model 52 in which a p53 R174P mutation was introduced, was defective in apoptosis while inducing cell cycle arrest. The expression changes observed in vivo in a series of Spalax target genes are in accordance with our previous in vitro results, 24,26 and the variations observed by different p53 mutants. 53 Inhibition of apoptosis is one of the key features of cancer and in many cancer types where apaf1 loss is evident.…”
Section: Spalax P53 Is Functionally Biased Against Apaf1 and Towards supporting
confidence: 78%
See 1 more Smart Citation
“…50,51 In addition, a mouse model 52 in which a p53 R174P mutation was introduced, was defective in apoptosis while inducing cell cycle arrest. The expression changes observed in vivo in a series of Spalax target genes are in accordance with our previous in vitro results, 24,26 and the variations observed by different p53 mutants. 53 Inhibition of apoptosis is one of the key features of cancer and in many cancer types where apaf1 loss is evident.…”
Section: Spalax P53 Is Functionally Biased Against Apaf1 and Towards supporting
confidence: 78%
“…45 We have previously demonstrated, in vitro, that Spalax p53 is functionally biased toward G 1 arrest and against apoptosis. 24,26 In particular, we have shown that apaf1, a critical regulator of apoptosis in response to several cellular stresses, including hypoxia, 46 was completely inactivated by Spalax p53. "Humanization" of Spalax p53 at position 174, Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…The subterranean mole rat (Spalax) thus provides a unique natural model, because it has evolved adaptive strategies to cope with extreme underground conditions of hypoxic stress (20). The high tolerance of Spalax to hypoxia seems related to a wide array of respiratory and cardiovascular adaptations, as reflected in structural and functional properties of several hypoxia-related genes including EPO (21), EPO-R (22), VEGF (23,24), HIF-1 (24,25), and p53 (26,27). The sequence of Spalax EPO-R (sEPO-R) exhibits unique features compared with EPO-R of other mammals (22).…”
Section: Erythropoietic Functions Of Erythropoietin (Epo) Are Mediatementioning
confidence: 99%
“…Hypoxia tolerance mechanisms identified in Spalax as compared with R. norvegicus include blood properties, anatomical and biochemical changes in respiratory organs (2,4), and differences in the structure and function of a growing list of gene products (7)(8)(9)(10). Transcription patterns of genes related to hypoxic stress differ interspecifically in Spalax (5,11) and between Spalax and rat, involving key players such as erythropoietin (Epo) and its receptors, and hypoxia-inducible factor-1α (Hif-1α) (12,13).…”
mentioning
confidence: 99%